2021
DOI: 10.1073/pnas.2006478118
|View full text |Cite
|
Sign up to set email alerts
|

Loss of hepatic miR-33 improves metabolic homeostasis and liver function without altering body weight or atherosclerosis

Abstract: miR-33 is an intronic microRNA within the gene encoding the SREBP2 transcription factor. Like its host gene, miR-33 has been shown to be an important regulator of lipid metabolism. Inhibition of miR-33 has been shown to promote cholesterol efflux in macrophages by targeting the cholesterol transporter ABCA1, thus reducing atherosclerotic plaque burden. Inhibition of miR-33 has also been shown to improve high-density lipoprotein (HDL) biogenesis in the liver and increase circulating HDL-C levels in both rodents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 34 publications
6
20
0
Order By: Relevance
“…Interestingly, liver-specific ablation of miR-33 does not lead to increased body weight but rather improves regulation of glucose homeostasis. Hepatic deletion of miR-33 also increased circulating HDL-C levels which is consistent with the notion that ABCA1 is essential for RCT and is repressed by miR-33 [58].…”
Section: Micrornas (Mirnas)supporting
confidence: 86%
“…Interestingly, liver-specific ablation of miR-33 does not lead to increased body weight but rather improves regulation of glucose homeostasis. Hepatic deletion of miR-33 also increased circulating HDL-C levels which is consistent with the notion that ABCA1 is essential for RCT and is repressed by miR-33 [58].…”
Section: Micrornas (Mirnas)supporting
confidence: 86%
“…Bone marrow transplant from miR-33-deficient animals into LDLR knockout mice did not result in the obesity or metabolic dysfunction observed in miR-33/LDLR double knockout animals, suggesting that macrophages and other hematopoietic cells were not responsible for driving this phenotype (Price et al, 2017). Consistent with this, characterization of macrophage-specific miR-33 conditional knockout mice also did not reveal any differences in body weight or circulating lipids under hyperlipidemic conditions (Price et al, 2021). In addition to demonstrating that neither direct effects of the liver, adipose tissue, or macrophages contribute substantially to the obesity phenotype of whole-body miR-33 knockout mice, this work also indicates that signaling from these peripheral tissues is not responsible for promoting the increased feeding that was observed.…”
Section: Hepatic Mir-33 In Atherosclerosissupporting
confidence: 73%
“…Dissecting the contribution of miR-33 in different metabolic tissues in regulating glucose homeostasis and obesity Considering the dramatic metabolic alterations in miR-33-deficient animals and the important implications of this for the potential use of miR-33 inhibitors to treat atherosclerosis and other conditions, our recent work has sought to determine what organs and/or cell types are primarily responsible for driving these metabolic changes. Development of conditional miR-33 knockout models has facilitated exploration of the specific roles of miR-33 in key metabolic tissues (Price et al, 2021). As the work of Horie et al indicated that changes in hepatic lipid metabolism may be responsible for driving the metabolic dysfunction of miR-33-deficient animals (Horie et al, 2013), our initial efforts focused on characterizing the impact of hepatocyte-specific miR-33 deficiency, by crossing conditional miR-33 knockout animals with mice expressing Albumin-Cre.…”
Section: Hepatic Mir-33 In Atherosclerosismentioning
confidence: 99%
See 2 more Smart Citations